The strength and selectivity of perfluorinated nano‐hoops and buckybowls for anion binding and the nature of anion‐π interactions. Issue 3 (11th February 2022) - Fan, Dan; Du, Juan; Dang, Jingshuang; Wang, Changwei; Mo, Yirong
Abstract: Perfluorinated cycloparaphenylenes (F‐[n]CPP, n = 5–8), boron nitride nanohoop (F‐[5]BNNH), and buckybowls (F‐BBs) were proposed as anion receptors via anion‐π interactions with halide anions (Cl −, Br − and I − ), and remarkable binding strengths up to −294.8 kJ/mol were computationally verified. The energy decomposition approach based on the block‐localized wavefunction method, which combines the computational efficiency of molecular orbital theory and the chemical intuition of ab initio valence bond theory, was applied to the above anion‐π complexes, in order to elucidate the nature and selectivity of these interactions. The overall attraction is mainly governed by the frozen energy component, in which the electrostatic interaction is included. Remarkable binding strengths with F‐[n]CPPs can be attributed to the accumulated anion‐π interactions between the anion and each conjugated ring on the hoop, while for F‐BBs, additional stability results from the curved frameworks, which distribute electron densities unequally on π‐faces. Interestingly, the strongest host was proved to be the F‐[5]BNNH, which exhibits the most significant anisotropy of the electrostatic potential surface due to the difference in the electronegativities of nitrogen and boron. The selectivity of each host for anions was explored and the importance of the often‐overlooked Pauli exchange repulsion was illustrated. Chloride anion turns out to be the most favorable anion for all receptors, due to the smallest ionic radius and the weakest destabilizing Pauli exchange repulsion. Abstract :